Rhizobacterial community structure in grafted tomato plants infected by Ralstonia solanacearum - Lisa Navitasari; TRI JOKO; RUDI HARI MURTI; TRIWIDODO ARWIYANTO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Navitasari L, Joko T, Murti RH, Arwiyanto T. 2020. Rhizobacterial community structure in grafted tomato plants infected by Ralstonia solanacearum. Biodiversitas 21: 4888-4895. Bacterial wilt disease caused by Ralstonia solanacearum is a devastating soil-borne vascular disease of tomato leading to a 100% yield loss. One of the alternatives to suppress the infestation of R. solanacearum infestation is the application of grafting techniques, which has been studied and successfully practiced by tomato growers. However, the infestation mode of R. solanacearum and the rhizobacterial community structure in grafted tomato plants are poorly reported. In this study, the rhizobacterial community structure in grafted tomato plants infected by R. solanacearum was investigated. The experiment was conducted on tomato germplasms with the implementation of tube grafting using resistant rootstocks (Amelia from Indonesia, H.7996 from Asian Vegetable Research Development Center/AVRDC) and susceptible scion (Servo from Indonesia). The rhizobacterial community structure was analyzed by metagenomic study under 16S rRNA genes sequencing with a distinct region (16SV3-V4) that was amplified using a specific primer (16SV4: 515F-806R) 5’-GTGCCAGCMGCCGCGGTAA and 5’GGACTACHVHHHTWTCTAAT. The results indicated that the grafted tomato plants and resistant rootstocks that were infected by R. solanacearum showed significantly lower intensity of bacterial wilt disease compared to the susceptible scion. The rhizobacterial community structure in the grafted tomato plants infected by R. solanacearum was indicated by predominant phyla of Proteobacteria, Firmicutes, and Actinobacteria with dominant genera of Pseudomonas and Bacillus. Besides, significant difference was also indicated by species of Geitlerinema sp. in the grafted tomatoes infected by R. solanacearum.